Analisis Yuridis Tindak Pidana Perjudian Dalam Qanun Aceh No. 6 Tahun 2014 Tentang Jinayat Dengan KUHP - Fahmi Jalil; Madiasa Ablisar; Edy Ikhsan; Mohammad Ekaputra (USU LAW JOURNAL, 2019)
Abstract. Real implementation of Aceh Qanun No. 6 of 2014 concerning Jinayat Law which excludes the provisions of gambling contained in KUHP which can be seen in a number of decisions of the Sharia Court, including the Decision of the Kuala Simpang Sharia Court No. 38/JN/2015/MSy-Ksg dated February 4, 2015 M to coincide with the 25th Rabiul Akhir 1437 H which states guilty in accordance with Article 18 of Qanun Aceh No. 6 of 2014 concerning Jinayat Law.   Keywords: jinayat, maisir and gambling